Analysis of the Effect of Loan to Deposit Ratio, Non Performing Loan & Capital Adequacy Ratio in Profitability - Limajatini Limajatini; Etty Murwaningsari; Sellawati Sellawati (eCo-Fin, 2019)
This study aims to analyze the effect of the Loan to Deposit Ratio (LDR), Non-Performing Loans (NPL) and Capital Adequacy Ratio (CAR) on Profitability in conventional banking companies listed on the Indonesia Stock Exchange 2013-2017 observation period. The data used in this study is obtained from the annual financial statements of banking companies on the Indonesia Stock Exchange through the official website on the Indonesia Stock Exchange website. Period of data under study from 2013 to 2017 (5 years). The sample collection using Purposive Sampling method and data analysis using multiple regression analysis with SPSS 23.0 program. From the results of hypothesis test simultaneously (F test) shows that LDR, NPL and CAR simultaneously have a significant effect on profitability, with a significance level of 0.000. While based on partial hypothesis test result (t test) shows that LDR variable does not affect to Profitability with significance level 0,767, NPL have negative and significant effect to Profitability with level of significance 0.000 and CAR have positive and significant effect to Profitability with level signifikan signifikan 0.000